Sosialisasi Pembuatan Larvasida Alami untuk Pencegahan DBD di Desa Reuloh Kecamatan Ingin Jaya Kabupaten Aceh Besar - Dewi Sartika; Iskandar Iskandar; Rifka Annisa Mardhatillah (Lembaga Pengembangan Kinerja Dosen, 2025)
Mosquitoes are often considered as carriers of disease. Various efforts have been made to reduce the mosquito population, including the use of chemical mosquito sprays. This is due to the lack of public knowledge about the use of plants around them such as citronella to be used as mosquito repellent and mosquito larvae killers. Therefore, activities were carried out that aimed to increase public understanding of the use of natural larvicide that focused on plants around them such as citronella which can be processed into useful materials. Through this socialization, we can provide useful information to the community, making them aware that citronella is not, method used is socialization and training for the community, regarding the use and manufacture of anti-mosquito Larvicide made from citronella. This activity consists of the preparation stage and the implementation stage. Based on the results of community service in Reuloh village, it shows high enthusiasm from the community and has a positive impact on knowledge about the dangers of mosquitoes and the manufacture and use of natural Larvicide ingredients as mosquito repellent and is believed to be able to kill larvae.